2010
DOI: 10.1063/1.3507891
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency droop alleviation in InGaN/GaN light-emitting diodes by graded-thickness multiple quantum wells

Abstract: InGaN/GaN light-emitting diodes ͑LEDs͒ with graded-thickness multiple quantum wells ͑GQW͒ was designed and grown by metal-organic chemical vapor deposition. The GQW structure, in which the well-thickness increases along ͓0001͔ direction, was found to have superior hole distribution as well as radiative recombination distribution by performing simulation modeling. Accordingly, the experimental investigation of electroluminescence spectrum reveals additional emission from the narrower wells within GQWs. Conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 17 publications
0
40
1
Order By: Relevance
“…InGaN/GaN multiple quantum well (MQW) lightemitting diodes (LEDs) have made significant progress in the past three decades. [1][2][3] The device performance is, however, still limited by Auger recombination, 4,5 charge separation, 6-9 current crowding, [10][11][12] insufficient hole injection, 9,[13][14][15][16][17][18] and electron overflow from the MQW active region. [19][20][21][22] In order to address these issues, a staggered quantum well architecture and also InGaN/GaN MQWs with Si-step-doped quantum barriers have been proposed to screen the quantum confined Stark effect (QCSE) and increase the spatial overlap of electron-hole wave functions, [7][8][9] while an improved current spreading can be obtained either by making the p-type layer more resistive or the p-contact layer more conductive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…InGaN/GaN multiple quantum well (MQW) lightemitting diodes (LEDs) have made significant progress in the past three decades. [1][2][3] The device performance is, however, still limited by Auger recombination, 4,5 charge separation, 6-9 current crowding, [10][11][12] insufficient hole injection, 9,[13][14][15][16][17][18] and electron overflow from the MQW active region. [19][20][21][22] In order to address these issues, a staggered quantum well architecture and also InGaN/GaN MQWs with Si-step-doped quantum barriers have been proposed to screen the quantum confined Stark effect (QCSE) and increase the spatial overlap of electron-hole wave functions, [7][8][9] while an improved current spreading can be obtained either by making the p-type layer more resistive or the p-contact layer more conductive.…”
mentioning
confidence: 99%
“…23 Furthermore, it has been reported that an enhanced hole injection efficiency can be obtained through utilizing a thinner quantum barrier 17,18 or a thinner quantum well. 16 Alternatively, InGaN quantum barriers can also promote the hole injection. 13 Recently, it has been found that pdoped quantum barriers favor the hole transport across the InGaN/GaN MQW region.…”
mentioning
confidence: 99%
“…For example, Lee et al enhanced the efficiency by grading InN fraction in InGaN quantum well structures [8]. Wang et al improved the efficiency by incorporating quantum wells with graded thickness [9]. Zhao et al employed thin AlInN barriers to suppress the thermionic carrier escape rate [10].…”
mentioning
confidence: 99%
“…The main physical mechanisms of efficiency droop effect have been investigated and proposed, including electron overflow [6][7][8][9], Manuscript poor hole injection [10][11][12], Auger recombination [13][14][15][16], carrier delocalization form In-rich region [17][18][19], polarization field [20][21][22][23], and junction heating [24][25]. However, the origin of the efficiency droop mechanism for nitride-based LEDs is still a controversial and uncertain issue until now.…”
Section: Introductionmentioning
confidence: 97%